Evaluating 130 microhaplotypes across a global set of 83 populations. (July 2017) - Kidd, Kenneth K.; Speed, William C.; Pakstis, Andrew J.; Podini, Daniele S.; Lagacé, Robert; Chang, Joseph; Wootton, Sharon; Haigh, Eva; Soundararajan, Usha
Highlights: Highly polymorphic multi-SNP microhaplotypes (<300 bp in extent) are common. We characterized 130 microhaps on 83 global populations using statistical phasing. Many of the microhaplotypes characterized are worth converting to MPS. Phase known microhaps can qualitatively identify and help deconvolute mixtures. Forensics can also use microhaps in identity, ancestry, and lineage/family studies. Abstract: Today the primary DNA markers used in forensics are short tandem repeat (STR) polymorphisms (STRPs), initially selected because they are highly polymorphic. However, the increasingly common need to deal with samples with a mixture of DNA from two or more individuals sometimes is complicated by the inherent stutter involved with PCR amplification, especially in strongly unbalanced mixtures when the minor component coincides with the stutter range of the major component. Also, the STRPs in use provide little evidence of ancestry of a single source sample beyond broad "continental" resolution. Methodologies for analyzing DNA have become much more powerful in recent years. Massively parallel sequencing (MPS) is a new method being considered for routine use in forensics. Primarily to aid in mixture deconvolution and avoid the issue of stutter, we have begun to investigate a new type of forensic marker, microhaplotype loci, that will provide useful information on mixtures of DNA and on ancestry when typed using massively parallel sequencing (MPS). We have identified 130 loci and estimated their haplotype (allele) frequencies in 83 different population samples. Many of these loci are shown to be highly informative for individual identification and for mixture identification and deconvolution.